G346 Cyphp evelina london new care model to improve health, healthcare quality, and patterns of service use among children and young people. (May 2019) - Wolfe, I; Lemer, C; Heys, M; Ingrassia, A; Newham, J; Forman, J; Satherley, R; Lingam, R
Abstract : Background: Children and young people's (CYP) healthcare outcomes should be better. CYP represent 25% of emergency department (ED) attendances; a 58% rise from 2007 to 2016, projected further 50%–60% by 2030. CYP from the most deprived backgrounds are 60%–70% more likely to attend A and E. Most ED attendances by CYP are manageable in primary or integrated care models, yet 85% are of low severity and the number of children presenting to ED with minor ailments increases 5% annually. Methods: CYPHP is a clinical academic partnership for health system strengthening. Model design included analysis of segmented population need, systematic literature reviews, co-production with families and professionals. Health promotion and self-management materials had extensive patient and public involvement. Implementation was agreed for 120, 000 CYP. CYPHP delivers practical results and iterative learning as a QI programme, and is evaluating the service as to research standards by a cluster randomised control trial (cRCT) with nested process evaluation and qualitative studies on health, healthcare quality, patterns of healthcare use, and cost effectiveness. Results: CYPHP's child and family-centred care coordinates across primary, community, and hospital settings to better integrate physical and mental healthcare for CYP's social context. Care is delivered by multidisciplinary teams and includes health promotion, proactive case-finding, biopsychosocial assessment, self-referral via a patient portal, and holistic tailored care. Early results indicate a reduction of 72 ED contacts per 100 children with asthma, 30 for children with epilepsy, 15 for children with constipation. Estimated cost savings per 100 asthma patients >£15, 000, for epilepsy >£6, 000, for constipation >£3000. Of the first 200 patients with ongoing conditions, most were from socially deprived areas: 68% were from black and minority ethnic groups, suggesting that the CYPHP population health approach provides care for those with greatest need. The average referral-to-treatment time for CYPHP's Child Health Clinics is 18 days. Families report more confidence in managing their child's condition out of the hospital. Implications: CYPHP is implementing and evaluating a new model of care to improve health, healthcare quality, and outcomes for local CYP, contribute generalizable evidence about children's health services and systems, and shape child health policy. Early results suggest encouraging impact on access to care and patterns of healthcare use.